Mycobacteriophage CRB2 defines a new subcluster in mycobacteriophage classification - Suarez, Cristian Alejandro (2019)
Fil: Fil: Suarez, Cristian Alejandro. Universidad Nacional de Rosario. Facultad de Ciencias Médicas. Laboratorio de Microbiología Molecular; Argentina